Ordinary grace : a novel - Krueger, William Kent (New York : Atria Books, 2014)
Looking back at a tragic event that occurred during his thirteenth year, Frank Drum explores how a complicated web of secrets, adultery, and betrayal shattered his Methodist family and their small 1961 Minnesota community.
Includes topics & questiions for discussion.
Keywords: Families -- Minnesota -- Fiction; Murder -- Minnesota -- Fiction; Grief -- Fiction; Bildungsromans; Detective and mystery stories